Centrin 2: A Novel Marker of Mature and Neoplastic Human Astrocytes - Degl’Innocenti, Elisa; Poloni, Tino Emanuele; Medici, Valentina; Recupero, Luca; Dell’Amico, Claudia; Vannini, Eleonora; Borello, Ugo; Mazzanti, Chiara Maria; Onorati, Marco; Dell’Anno, Maria Teresa (Frontiers in Cellular Neuroscience, 2022)
As microtubule organizing centers, centrosomes play a pivotal role in cell division as well as in neurodevelopment and neuronal maturation. Among centrosomal proteins, centrin-2 (CETN2) contributes also to DNA repair mechanisms which are fundamental to prevent genomic instability during neural stem cell pool expansion. Nevertheless, the expression profile of CETN2 in human neural stem cells and their progeny is currently unknown. To address this question, we interrogated a platform of human neuroepithelial stem (NES) cells derived from post-mortem developing brain or established from pluripotent cells, and demonstrated that while CETN2 retains its centrosomal location in proliferating NES cells, its expression pattern changes upon differentiation. In particular, we found that CETN2 is selectively expressed in mature astrocytes with a broad cytoplasmic distribution. We then extended our findings on human autoptic nervous tissue samples. We investigated CETN2 distribution in diverse anatomical areas along the rostro-caudal neuraxis and pointed out a peculiar topography of CETN2-labelled astrocytes in humans which was not appreciable in murine tissues, where CETN2 was mostly confined to ependymal cells. As prototypical condition with glial overproliferation, we also explored CETN2 expression in glioblastoma multiforme, reporting a focal concentration of CETN2 in neoplastic astrocytes. This study expands CETN2 localization beyond centrosomes and reveals a unique expression pattern which makes it eligible as a novel astrocytic molecular marker, thus opening new roads to glial biology and human neural conditions.